2013
DOI: 10.36691/rja614
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with bronchial asthma

Abstract: Background. To estimate interrelation of clinical and functional parameters and vessel tome regulating function of endothelium in patients with bronchial asthma. Methods. 126 patients with bronchial asthma have been examined, including 29 patients with mild bronchial asthma (the first group), 32 persons with moderate bronchial asthma (the second group), 40 respondents with severe asthma (the third group) and 25 patients with steroiddependent asthma (fourth group). The control group included 27 healthy voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This indicated that the ratio of estrogen to progesterone determines the expression of CD38 and the activity of ADPRC. The effects of estrogen and other steroid superfamily hormones on specific cell functions and hormone-induced gene expression in target cells are mediated by the cADPR-Ca 2+ release pathway (Dogan et al, 2002;Poltronieri et al, 2021;Sobko et al, 2013).…”
Section: Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the ratio of estrogen to progesterone determines the expression of CD38 and the activity of ADPRC. The effects of estrogen and other steroid superfamily hormones on specific cell functions and hormone-induced gene expression in target cells are mediated by the cADPR-Ca 2+ release pathway (Dogan et al, 2002;Poltronieri et al, 2021;Sobko et al, 2013).…”
Section: Hormonesmentioning
confidence: 99%
“…This indicated that the ratio of estrogen to progesterone determines the expression of CD38 and the activity of ADPRC. The effects of estrogen and other steroid superfamily hormones on specific cell functions and hormone‐induced gene expression in target cells are mediated by the cADPR‐Ca 2+ release pathway (Dogan et al, 2002; Poltronieri et al, 2021; Sobko et al, 2013). l ‐thyroxine regulates the expression of proapoptotic biomarkers by regulating calcium mobilization, mediated by calmodulin, thus protecting renal cells from ischemia‐reperfusion injury and changing renal toxicity (El‐Hamoly et al, 2017).…”
Section: Adprc Activity Regulatorsmentioning
confidence: 99%